2020
DOI: 10.18502/ijaai.v19i6.4927
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Multisystem Inflammatory Syndrome: A Systematic Review and Meta-analysis

Abstract: The prevalence of multisystem inflammatory syndrome in children (MIS-C) has increased since the coronavirus disease 2019 (COVID-19) pandemic started. This study was aimed to describe clinical manifestation and outcomes of MIS-C associated with COVID-19. This systematic review and meta-analysis were conducted on all available literature until July 3rd, 2020. The screening was done by using the following keywords: (“novel coronavirus” Or COVID-19 or severe acute respiratory syndrome coronavirus 2 (SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 40 publications
11
37
1
8
Order By: Relevance
“…Kaushik et al [26] found similar imaging abnormalities in 90 (13.7%) of the patients, which resembled the findings in our case. A complete blood count tends to show elevated neutrophils and reduced lymphocytes which were replicated in our findings [24][25][26]. e laboratory findings in MIS-C uniformly indicate ≥4 elevated inflammatory markers such as erythrocyte sedimentation rate, C-reactive protein, procalcitonin, and ferritin, with a simultaneous rise in the International Normalized Ratio, fibrinogen, D-dimer, alanine aminotransferase, lactate dehydrogenase, interleukin-6 and interleukin-8, and cardiac markers (B-type natriuretic peptide, N-terminal proBtype natriuretic peptide, and troponin) [14,[27][28][29].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Kaushik et al [26] found similar imaging abnormalities in 90 (13.7%) of the patients, which resembled the findings in our case. A complete blood count tends to show elevated neutrophils and reduced lymphocytes which were replicated in our findings [24][25][26]. e laboratory findings in MIS-C uniformly indicate ≥4 elevated inflammatory markers such as erythrocyte sedimentation rate, C-reactive protein, procalcitonin, and ferritin, with a simultaneous rise in the International Normalized Ratio, fibrinogen, D-dimer, alanine aminotransferase, lactate dehydrogenase, interleukin-6 and interleukin-8, and cardiac markers (B-type natriuretic peptide, N-terminal proBtype natriuretic peptide, and troponin) [14,[27][28][29].…”
Section: Discussionsupporting
confidence: 82%
“…In three systematic reviews and meta-analyses of MIS-C, the pulmonary radiological features were described as infiltrates or opacities which were reported by Yasuhara et al among 131 subjects (38.3% [95% CI, 29.7–46.9]) [ 24 ]. Badaradan et al [ 25 ] found across 8 studies that 45.9% (95% CI, 34.1%–58.2%) of the patients had abnormalities on chest X-ray or computed tomography which included ground-glass opacity, interstitial abnormalities, or local patchy shadowing. Kaushik et al [ 26 ] found similar imaging abnormalities in 90 (13.7%) of the patients, which resembled the findings in our case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prevalence of severe or critical disease is 10.6, 7.3% and about 4% in children aged <1 year, 1-5years and 6-15 year, respectively (11). Few months after the onset of the pandemic, a series of reports around the world described clusters of children and adolescents presenting with a lifethreatening, hyperinflammatory syndrome, named Kawasakilike syndrome (8,12), Pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) (13) or Multisystem Inflammatory Syndrome in Children (MIS-C) (14). The pathogenesis of MIS-C is still unknown, although it has been suggested that this syndrome occurs while the immune system is activated against the SARS-CoV-2 virus (15).…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…However, the United Kingdom's National Health Service alerted paediatricians regarding a new outbreak of a Kawasaki-like disease, which was temporally associated with COVID-19 and revealed clinical evidence of SARS-CoV-2 infection [5,6]. Affected children appear to have severe illness, including fever and multi-organ inflammation (shock, cardiac, respiratory, renal, gastrointestinal, or neurological symptoms) similar to the cytokine storm in Kawasaki disease (KD) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%